The effect of self expressive value and perceived value on Malaysian cosmetic brand loyalty: the mediating role of brand identification & word of mouth / Norzalita Abd Aziz and Hafaz Ngah. - Abd Aziz, Norzalita; Ngah, Hafaz (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2019)
Competition in the cosmetic industries is stiff as more industrial players are striving to capture the market in Malaysia. Cosmetics play a crucial role in addressing image or presentation to others. There is a dearth of information concerning consumers’ perception of the Malaysian Cosmetic Brand (MCB). This article aims to understand how Self-Expressive Value (SEV) and Perceived Value (PV) relate to Brand Identification (BI) and Word of Mouth (WOM) among consumers. Using a self-administered questionnaire contributed to a total of 261 usable respondents and the PLS results indicate that there is a significant relationship between PV and SEV on BI and WOM while BI and WOM meditate the relationship between PV and SEV with Customer Loyalty. This article provides some insights on current local consumers perception and behaviour towards Malaysian cosmetic brands. Thus, MCB marketers need to emphasise the value of their products and reflect consumers’ self-expressive value that will enhance their brand identification and WOM among consumers which may lead to loyalty among users.